Thromboses in tuberculosis are linked to antiphosphatidylethanolamine antibodies levels: A cross-sectional study. (May 2019) - Bessis, Simon; Bertin, Daniel; Million, Matthieu; Meddeb, Line; Drancourt, Michel; Lagier, Jean-Christophe; Mège, Jean-Louis; Bardin, Nathalie; Brouqui, Philippe
Abstract: Venous thromboses have been associated with tuberculosis, but the relationship with circulating anticoagulant has not been studied yet. In a cohort of 48 patients with tuberculosis, 22.9% of them presented with venous thromboses significantly associated with dose dependent level of antiphosphophatidyl-ethanolamine antibodies.